Vapour-liquid phase behaviour of primitive models of ionic liquids confined in disordered porous media - T. Hvozd; T. Patsahan; Yu. Kalyuzhnyi; O. Patsahan; M. Holovko (Condensed Matter Physics, 2024)
We  develop a theory for the description  of  ionic liquids (ILs) confined in a porous medium formed by a matrix of immobile randomly placed uncharged  particles. The IL is modelled as an electroneutral  mixture of hard-sphere anions and flexible linear chain cations, represented by tangentially bonded hard spheres with the charge located on one of the terminal beads. The theory combines  a  generalization of the scaled particle theory, Wertheim's thermodynamic perturbation theory, and the associative mean-spherical approximation  and allows one to obtain analytical expressions for the pressure and chemical potentials of the  matrix-IL system. Using the theory, we calculate the vapour–liquid phase diagrams for two versions of the IL model, i.e., when the cation is modelled as a dimer and as a chain, in a complete association limit. The effects of the matrix confinement  and of the  non-spherical shape of the cations on the vapour-liquid phase diagrams are studied.